Discovery of Four Species of Trichogramma (Hymenoptera, Trichogrammatidae), New for the Fauna of England - Fursov, V.N. (Вестник зоологии, 2000)
Four species of Trichogramma Westw. are recorded at the first time for the fauna of England – T. danubiense Birova et Kazimirova (known only from Slovakia), T. talitzkii Djuritsh (known from Moldova), T. lacustre Sorokina (known from Russia), T. daumalae Dugast et Voegele (known from France and Bulgaria). Descriptions of species and diagnoses are given. Впервые указаны для фауны Англии 4 вида рода Trichogramma Westw. T. danubiense Birova et Kazimirova (известен только из Словакии), T. talitzkii Djuritsh (известен из Молдовы), T. lacustre Sorokina (известен из России), T. daumalae Dugast et Voegele (известен из Франции и Болгарии). Дано описание видов и дан их дифференциальный диагноз.